CO2 Hydrogenation to Methanol with Ga‐ and Zn‐Doped Mesoporous Cu/SiO2 Catalysts Prepared by the Aerosol‐Assisted Sol‐Gel Process. Issue 23 (15th October 2020) - Paris, Charlie; Karelovic, Alejandro; Manrique, Raydel; Le Bras, Solène; Devred, François; Vykoukal, Vit; Styskalik, Ales; Eloy, Pierre; Debecker, Damien P.
Abstract: The preparation of copper‐based heterogeneous catalysts dedicated to the hydrogenation of CO2 to methanol typically relies on multi‐step procedures carried out in batch. These steps are precisely tailored to introduce the active phase (Cu) and the promoters (e. g., zinc, gallium) onto a preformed support to maximize catalyst performance. However, each process step can be associated with the formation of waste and with the consumption of energy, thereby negatively impacting the environmental performance of the overall catalyst preparation procedure. Here, a direct and continuous production process is proposed for the synthesis of efficient catalysts for the CO2 ‐to‐methanol reaction. Gallium‐ and zinc‐promoted mesoporous Cu−SiO2 catalysts were prepared in one step by the aerosol‐assisted sol‐gel process. The catalysts consisted of spherical microparticles and featured high specific surface area and pore volume, with interconnected pores of about 6 nm. A strong promoting effect of Ga and Zn was highlighted, boosting the selectivity for methanol at the expense of CO. Upon calcination, it was shown that Cu species (initially trapped in the silica matrix) underwent a migration towards the catalyst surface and a progressive sintering. After optimization, the catalysts obtained via such direct, continuous, simple, and scalable route could compete with the best catalysts reported in the literature and obtained via multi‐step approaches. Abstract : One step, many benefits : Ga‐ and Zn‐doped Cu‐based hydrogenation catalysts are prepared in one step via aerosol‐assisted sol‐gel chemistry and reach good performance in the CO2 ‐to‐methanol reaction. The synthesis method is direct, simple, continuous, and scalable. It leads to high‐surface‐area mesoporous catalysts with the dopant dispersed in the silica matrix and copper nanoparticles at the catalyst surface.